Hubungan Pemberian MP-ASI Dini Dengan Status Gizi dan Pertumbuhan Bayi Usia 6 Bulan di Desa Cikidang Kecamatan Lembang - Mastiur B Julianti; Atit Hadiati; Ellis Siti Nurwulan (STIKes Karsa Husada Garut, 2015)
The level of nutrition and the growthis influenzed by giving complementary breastfeeding. Giving early complementary breastfeeding can increase the baby morbidity, many kinds of problem, which happened will affect baby’s growth. The function of this research is to know about the correlation between giving early complementary breastfeeding with the level of nutrition and the growth of the 6 month baby.the baby is person who has age zero to one years. Early complementary breastfeeding is meal or drink that given to the babies before six month. Growth related to the changing of large, number, size and the function of the cells. The level of nutrition is nutrition condition at the baby. This research is using analytical method with Cross Sectional approach. The population of this research is the babies, who is in age 6-11 month in cikidang village as much as 60 babies. The sample of this research is the babies, who ar in age 6-11 month as much as 49 babies. The sampling technique of this research is Total Sampling. According to the result of Statistic-test by using Chi-Square, it found that p-value is 0,050, it means that it has significant relationship between early-complementary breastfeeding with the level of nutrition. The result of statistic-test, it found p-value is 0,387, it means there is slight relationship between early-complementary breastfeeding with the length of the baby’s body. The result of statistic-test found p-value is 0,022, it means there is significant relationship between the level of nutrition with baby’s body proportion. The conclusion of this research is almost all respondent have good-level of nutrition, the length and the body’s proportion is normal, whether given early complementary feeding or without given early complementary feeding. The advice is we hope this research can give advices for official village to create a group of villagers to be aware of the food’s nutrition by cook. So it can be knowledge and good habit for them.